Sustainable and carbon-neutral green diesel synthesis with thermochemical and electrochemical approach: Techno-economic and environmental assessments. (15th February 2022) - Choe, Changgwon; Lee, Boreum; Lim, Hankwon
Highlights: Techno-economic and environmental analyses of green diesel synthesis were conducted. Different syngas production pathways and renewable energy resources were considered. Economic and environmental sustainability for green diesel synthesis was confirmed. Potential strategy of sustainable green diesel synthesis pathway was investigated. Abstract: In this work, techno-economic and environmental assessments were conducted for green diesel production. In particular, two green diesel production pathways through thermochemical and electrochemical processes, which have different syngas production methods, were covered to evaluate the sustainability in terms of economic and environmental perspectives. The process modeling was performed for three cases, classifying cases according to the component composition, and verified by comparing the physical properties of conventional diesel and green diesel produced from syngas. From process modeling results, case 2 has the most relevant properties of conventional diesel showing the potential for alternative diesel fuel. With the process modeling results, cost estimation was carried out to calculate the current unit diesel production costs for three scenarios (according to the renewable energy sources); 0.0507, 0.0647, and 0.0547 $ MJ −1 via the thermochemical process and 0.0477, 0.0606, and 0.0514 $ MJ −1 through the electrochemical process for hydropower, solar PV, and onshore wind, respectively, showing the infeasibility due to the lower conventional ones (0.0164–0.0276$ MJ −1 ). To make the green diesel production attractive, uncertainty analysis and projected cost analysis were conducted to obtain the possible cost ranges due to the cost fluctuations of key economic parameters and the estimated unit diesel production cost in 2030, with the projected levelized cost of electricity by 2030 and learning rates by cumulative production of H2 and CO demands. Moreover, environmental assessment should be performed to identify whether the green diesel production is more eco-friendly or not than conventional one, by considering direct emission and indirect one emitted from energy consumption. From environmental assessment results, lower CO2 emissions can be investigated according to the renewable energy sources for green diesel production and the electrochemical green diesel production with onshore wind has the lowest CO2 emission among all scenarios covered in this work.